Diode laser based light sources for biomedical applications. Issue 5 (21st December 2012) - Müller, André; Marschall, Sebastian; Jensen, Ole Bjarlin; Fricke, Jörg; Wenzel, Hans; Sumpf, Bernd; Andersen, Peter E.
<x xml:space="preserve">Abstract</x> Diode lasers are by far the most efficient lasers currently available. With the ever‐continuing improvement in diode laser technology, this type of laser has become increasingly attractive for a wide range of biomedical applications. Compared to the characteristics of competing laser systems, diode lasers simultaneously offer tunability, high‐power emission and compact size at fairly low cost. Therefore, diode lasers are increasingly preferred in important applications, such as photocoagulation, optical coherence tomography, diffuse optical imaging, fluorescence lifetime imaging, and terahertz imaging. This review provides an overview of the latest development of diode laser technology and systems and their use within selected biomedical applications. 670 nm external cavity diode laser for Raman spectroscopy built on a 13 × 4 mm2 microbench (Copyright FBH/Schurian.com). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>